The influence of planting distance on seagrass (Enhalus acoroides) seedling growth - Haniifah Nur Faatinah Puruhito; Indri Addini; Aditya Hikmat Nugraha (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2024)
Seagrass restoration practice of transplanting grown seagrass from a donor to the planting site is discovered to disrupt the existing ecosystems. An alternative method includesthe use of seedlings, which requires a protected germination environment to survive. At the initial stage, the seedlings need adequate space for growth and expansion of root systems. However, cultivating seagrass seedlings in aquariums is challenging due to limited space. Therefore, this study aimed to investigate the growth and development of aquarium-cultured seagrass seedlings and evaluate the impact of different spacing on growth. Seedlings were cultivated in the laboratory under 2 treatments, each lasting 3 months. Enhalus acoroides seedlings collected from Dompak Island, Tanjungpinang, were used with varying planting distances for each treatment. The results showed that Treatment A (4 cm spacing) had a lower survival rate (66.73%) compared to TreatmentB (1.5 cm spacing) (97.78%) due to a fungus outbreak.However, Treatment B had slower growth than A, suggesting potential problems with water quality and increased competition for resources in denser plantings. In this study, the significance of planting spacing was outlined and a statistically significant difference was discovered in seagrass growth between various treatments (P0.05). A rapid growth rate of 2.08-3.02 mm/day was observed in leafs, which exceeded the value observed in previous investigations conducted under similar conditions and species. It was important to acknowledge that leaf length was also 17.5-21.6 cm, exceeding the values observed in another experiment using lab-cultured E. acoroides. Root lengths were comparatively shorter (7.6-8.2 cm), which signified the dynamic nature of seagrass development. In conclusion, addressing environmental conditions and optimizing planting spacing, was essential for sustainable growth.Keywords:EnhalusGrowthSeagrassSeedlingsSpacing